The Impact of Rubber and Dumbble Training on Improving The Gyaku Tsuki Ability of Inkanas Karate Athletes, North Luwu - Kartini, Kartini; Asrullah, Asrullah; Hakim, Hikmad; Arfanda, Poppy Elisano (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This study aims to analyze the impact of rubber and dumbbell training on improving gyaku tsuki ability in Inkanas Luwu Utara karate athletes. Gyaku tsuki is an important basic technique that requires strength, speed, and technique. The research method used was an experiment with two groups of athletes. The first group (Group Rubber) underwent training using rubber, while the second group (Group Dumbbell) used dumbbells. The study was conducted for 16 meetings with measurements of gyaku tsuki performance before and after the training program. The results showed that both training methods improved gyaku tsuki ability, but the group using rubber showed a more significant increase. These findings provide insight for coaches and athletes in designing more effective training programs.